Preconditioning of an underflow during ice-breakup in a subarctic lake - Forrest, AL; Andradottir, HO; Laval, BE (Aquatic Sciences, 2012)
The fate of inflows into lakes has been extensively studied during summer stratification but has seen relatively little focus during the weak winter stratification, with or without ice-cover. Field observations are presented of groundwater inflow into a shallow bay of a subarctic lake. Atmospheric forcing of the bay during the study period was extremely variable and coincided with spring ice-cover break-up. Two dominant wind regimes were identified; (1) weak wind-forcing (wind speed <5 m s -1 or land-fast ice-cover), and (2) strong wind-forcing (wind speed >5 m s -1 and open water). At a relatively constant temperature of ~3.3C, the groundwater inflow was closer to the temperature of maximum density than the water in the main body of the lake, which during the observed winter stratification is ~1.2C. During weak wind-forcing, the stratification within Silfra Bay approximated two-layers as this denser groundwater formed a negatively buoyant underflow. A calculated underflow entrainment rate of 2. 8 10 -3 agrees well with other underflow studies. During strong wind-forcing, the water column out to the mouth of the bay became weakly stratified as the underflow was entrained vertically by wind-stirring. Observed periods of mixing can be predicted to occur when turbulent kinetic energy (TKE) production by wind stirring integrated over the underflow hydraulic residence time in the bay exceeds the potential energy associated with the stratification. A decrease of ice cover, as observed in the studied subarctic lake over the last decade, will result in the underflow being more frequently exposed to the strong wind-forcing regime during winter, thereby altering the winter distribution of groundwater inflow within the lake. 2011 Springer Basel AG.